Spiritual Health and Persons with Intellectual Disability: A Review - Merrick, Joav (Journal of religion, disability & health, 2001)
Religion and faith seems to play an important part in medicine and health in spite of the advances of modern medicine. This presentation reviews the present knowledge of the interaction between prayer, religious activity, distant healing and health in general and the few studies involving religion and persons with intellectal disability. Results from a recent study of spiritual health in residential centers for persons with intellectual disability are also reviewed. It is concluded that there indeed seems to be a connection between spiritual activities and physical health and well-being.